Perspektif Epistemologis dalam Design Thinking pada Pembelajaran Matematika: Systematic Literature Review - Silva P. D. Sagala; I Gusti Putu Sudiarta (FKIP Universitas Mataram, 2026)
Design thinking has been increasingly applied in mathematics education due to its potential to promote active, contextual, and student-centered learning. However, studies that explicitly examine this approach from an epistemological perspective in mathematics education remain limited. This study aims to analyze how epistemology in mathematics education is discussed in the literature, identify the epistemological foundations underlying the application of design thinking, and examine its epistemological implications for mathematics learning. This research employed a Systematic Literature Review (SLR) following the PRISMA guidelines. Articles were collected from Google Scholar within the publication period of 2014-2024. A multi-stage screening process involving title screening, abstract screening, and full-text review resulted in 12 relevant articles for final analysis. The findings indicate that the implementation of design thinking in mathematics education is predominantly grounded in constructivist and pragmatic epistemological perspectives, which view knowledge as actively constructed through experience, reflection, and authentic problem-solving. Epistemologically, design thinking supports a shift from procedural-oriented instruction toward meaningful, collaborative, and contextual mathematics learning. The novelty of this study lies in its explicit integration of epistemological perspectives to analyze design thinking in mathematics education, offering a conceptual contribution that extends beyond previous SLR studies. Keywords: epistemology, design thinking, mathematics education, systematic literature review